Conhecimento dos enfermeiros de atenção básica referente aos resultados do Papanicolau - Gonçalves, Roberta Fernandes (2018)
The most effective method of preventing cervical cancer is still the cervical screening test (Pap Pest or Smear Test) or cytopathologic cytology that can be performed by doctors and nurses. However, the interpretation of the result may be a challenge and may lead to inappropriate conduct regarding the referral of the patient for treatment. Therefore, the present study aimed to evaluate the level of knowledge of nurses in reading the Smear Test's results in the Public Health System of the city of Bauru, São Paulo, to enable the standardisation of these professionals in regards to the interpretation of the results, according to the protocols of the Ministry of Health. Initially, an online questionnaire was applied to professionals who perform Pap Test. Data were tabulated, analysed, and presented by descriptive statistics. A digital manual was developed to enable the reading and interpretation of the oncotic cytology results, according to the questions raised in the questionnaire, aiming to optimize the nurses' conduct for a more dynamic, fast diagnosis and, consequently, to improve the prognosis and increase the chance of treatment and cure. The manuals were scanned and forwarded online to all network nurses, all Public Health and Family Health Units of the municipality of Bauru. The results show a higher frequency of female nurses, in the age group of 36 to 40 years, with a time of practice in the area from six to ten years, who received training in oncology cytology and performed it once or twice a week; the participants also declared that they were able to analyse the results of the examinations; the time from the examination to the arrival of the result to the referral service is, on average, 55 days. It was concluded that most of the answers were positive, but with some deficiencies, which justifies a better qualification in this area.